2021
DOI: 10.1093/nar/gkab096
|View full text |Cite
|
Sign up to set email alerts
|

Single bacterial resolvases first exploit, then constrain intrinsic dynamics of the Holliday junction to direct recombination

Abstract: Homologous recombination forms and resolves an entangled DNA Holliday Junction (HJ) crucial for achieving genetic reshuffling and genome repair. To maintain genomic integrity, specialized resolvase enzymes cleave the entangled DNA into two discrete DNA molecules. However, it is unclear how two similar stacking isomers are distinguished, and how a cognate sequence is found and recognized to achieve accurate recombination. We here use single-molecule fluorescence observation and cluster analysis to examine how p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…In wide-field total internal reflection fluorescence microscopy (TIRFM)-based smFRET, the system of interest is immobilized on a surface, typically on a functionalized quartz surface. With significantly high time resolution offered by modern scientific CMOS cameras, simultaneous observation of hundreds of individual molecules in action for a longer period of time has become possible ( Ray et al, 2021 ). As the distance between the donor and the acceptor fluorophores changes, the fluorescence intensities from them change in an anticorrelated fashion.…”
Section: Real-time Monitoring Of Conformation Transition Using Smfretmentioning
confidence: 99%
“…In wide-field total internal reflection fluorescence microscopy (TIRFM)-based smFRET, the system of interest is immobilized on a surface, typically on a functionalized quartz surface. With significantly high time resolution offered by modern scientific CMOS cameras, simultaneous observation of hundreds of individual molecules in action for a longer period of time has become possible ( Ray et al, 2021 ). As the distance between the donor and the acceptor fluorophores changes, the fluorescence intensities from them change in an anticorrelated fashion.…”
Section: Real-time Monitoring Of Conformation Transition Using Smfretmentioning
confidence: 99%
“…Dynamics intrinsic to HJ were analyzed to find cognate sequence and achieve site-specific cleavage [88] Kinetic details of GEN1 dimers decomposed HJ were explained [91] Strand sequence A model of reversible branch migration in mobile 3WJ with trinucleotide repeats was proposed, which may help the treatment of diseases [93] RNA secondary structure Metal cation Na + and K + were proved to facilitate the formation of RNA tetraloop-tetraloop receptor tertiary motif [101] Small molecules in solution…”
Section: Solvent Conditionmentioning
confidence: 99%
“…The experimental results indicated that RuvA bounded to the HJ stably through electrostatic interaction to prevent its conformational dynamics. Recently, a more detailed report [ 88 ] not only focused on the binding properties of RuvC and HJ, but also dissected the behavior of the HJ-RuvC complex to continue cleavage after recognizing the cleavage-active sequence. They discovered that RuvC can achieve site-specific cleavage, which may inspire further research using this mechanism of RuvC.…”
Section: Investigating the Structural Changes Under Various Circumstancesmentioning
confidence: 99%
See 1 more Smart Citation
“…( 8 ) and Sujay et al. ( 9 ) combined smFRET and site-specific labelling of DNA substrates to test length-dependent compaction of telomeres and the dynamics of the E. coli resolvase RuvC during Holliday junction resolution, respectively. In addition to the changes in intensity reporting proximity, smFRET experiments provide a wealth of kinetic information spanning multiple imaging channels.…”
mentioning
confidence: 99%